Photoinduced electronic and ionic effects in strontium titanate. Issue 23 (9th November 2021) - Siebenhofer, Matthäus; Viernstein, Alexander; Morgenbesser, Maximilian; Fleig, Jürgen; Kubicek, Markus
Abstract : Illumination of SrTiO3 induces a multitude of electronic and ionic effects. Recent advances in photoconductivity, photoluminescence, photovoltage, photochromism and photocatalysis are highlighted. Abstract : The interaction of light with solids has been of ever-growing interest for centuries, even more so since the quest for sustainable utilization and storage of solar energy became a major task for industry and research. With SrTiO3 being a model material for an extensive exploration of the defect chemistry of mixed conducting perovskite oxides, it has also been a vanguard in advancing the understanding of the interaction between light and the electronic and ionic structure of solids. In the course of these efforts, many phenomena occurring during or subsequent to the illumination of SrTiO3 have been investigated. Here, we give an overview of the numerous photoinduced effects in SrTiO3 and their inherent connection to electronic structure and defect chemistry. In more detail, advances in the fields of photoconductivity, photoluminescence, photovoltages, photochromism and photocatalysis are summarized and their underlying elemental processes are discussed. In light of recent research, this review also emphasizes the fundamental differences between illuminating SrTiO3 either at low temperatures (200 °C), where in addition to electronic processes, also photoionic interactions become relevant. A survey of the multitude of different processes shows that a profound and comprehensive understanding of the defect chemistry and its alteration under illumination is both vital to optimizing devices and to pushing the boundaries of research and advancing the fundamental understanding of solids.